DYADIC COPING DAN KEPUASAN PERNIKAHAN PASANGAN SUAMI ISTRI DENGAN SUAMI DIABETES MELITUS TIPE II (Jurnal Psikologi Udayana, 2016)
This study was conducted to examine the relationship between dyadic coping and marital satisfaction in couples with husband diabetes mellitus type II. Dyadic coping is an interpersonal process that involves both partners in a marriage relationship (Bodenmann, 2005), dyadic coping were measured using dyadic coping scale. Marital satisfaction is an evaluation of the areas in marriage that includes communication, leisure activities, religious orientation, conflict resolution, financial management, sexual relationships, family and friends, equalitarian roles, and parenting styles (Olson & Olson, 2000), marital satisfaction measured using marital satisfaction scale. This research method is quantitative method with the research subjects were married couples with husband diabetes mellitus type II, married with a minimum marriage age of 5 years, and not being bedridden (n = 80). Technique sampling in this research is purposive sampling. The data were analyzed using simple linear regression . The results of simple linear regression show that the value of significant level 0.001 (p